계획된 행동이론을 활용한 일부 여대생의 운동실천 관련요인 - 이병훈(Byung-Hoon Lee); 고대식(Dae-Sik Ko); 배상열(Sang-Yeol Bae); 노지숙(Ji-Sook Noh); 최문실(Moon-Sil Choi); 박종(Jong Park) (保健敎育健康增進學會誌, 2010)
Objectives: This study aims to identify factors related to exercise of some female college based on Theory of planned behavior. Methods: This study surveyed 500 female students attending a university to answer to self-reported questions using a questionnaire from May 3 to May 22 2010 and used 462 copies of the responses except insincere ones for the final analysis. Results: Of the 462 subjects, 30.7%(142) did regular exercise more than 3 times a week. As a result of the univariate analysis, there were relations between drinking, need of Exercise, attention to health, health habits, perceived behavior control and intention of exercise, and regular exercise. As a result of the multiple Logistic regression, there was a statistically significant relation between regular exercise and perceived behavior control and intention and drinking. Conclusion: This study identified that there were relations between drinking, perceived behavior control and intention of female college students and their regular exercise. Therefore, to promote their regular exercise, it is suggested that educational programs which consider such factors should be developed.